2015
DOI: 10.1038/srep10503
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of individual pulp fiber bonds quantifies the mechanisms of fiber bonding in paper

Abstract: The process of papermaking requires substantial amounts of energy and wood consumption, which contributes to larger environmental costs. In order to optimize the production of papermaking to suit its many applications in material science and engineering, a quantitative understanding of bonding forces between the individual pulp fibers is of importance. Here we show the first approach to quantify the bonding energies contributed by the individual bonding mechanisms. We calculated the impact of the following mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 35 publications
0
81
0
3
Order By: Relevance
“…5% and 10% replacement of base pulp. The performance of the prepared handsheets was evaluated experimentally and compared with the predictions by semi-empirical models and mechanistic models (Hirn and Schennach 2015).…”
Section: Introductionmentioning
confidence: 99%
“…5% and 10% replacement of base pulp. The performance of the prepared handsheets was evaluated experimentally and compared with the predictions by semi-empirical models and mechanistic models (Hirn and Schennach 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, recent results show that there is a high degree of bonding between fiber surfaces (Persson et al 2013, Hirn and Schennach 2015. Therefore, we neglected possible flaws in the bonding for reasons of simplification.…”
Section: Finite Element Discretizationmentioning
confidence: 99%
“…The cellulose material of the fibril is known to be strongly hydrophilic (see e.g. Hirn and Schennach 2015). So, the empty spaces between fibrils inside a bundle (about a few Nano meters) are expected to imbibe water strongly.…”
Section: Visualization Of Flow In Fibrous Layermentioning
confidence: 99%
“…Based on their study, each cellulose fiber is composed of micro-fibril bundles (diameters of 20-30 nm). Hirn and Schennach (2015) found out that fibers in a paper bond to each other by six different mechanisms: interdiffusion, mechanical interlocking, capillary forces, Coulomb forces, hydrogen bonding, and van der Waals forces. They concluded that, in contrast to general belief that favors hydrogen bonding, van der Waals bonds play the most important role.…”
Section: Introductionmentioning
confidence: 99%